Perbandingan Metode Isolasi DNA pada Produk Perikanan Segar dan Olahan: Comparison of DNA Isolation Methods for Fresh and Processed Seafood - Aninditya Artina Setiaputri; Giri Rohmad Barokah; Muh. Alsere Bardian Sahaba; Rahma Dini Arbajayanti; Nadia Fabella; Rizsa Mustika Pertiwi; Mala Nurilmala; Roni Nugraha; Asadatun Abdullah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Seafood product is an important commodity in the global trade market, however, seafood fraud has been increasingly reported. Therefore, a method to specifically identify species of seafood products is needed. DNA methods gain many interests for detection of seafood fraud due to its robustness. This study was aimed to determine the effectiveness of several methods for isolation of DNA from fresh and processed seafood. The DNA isolation methods used in this study were the CTAB DNAzol, TianGen, Qiagen, and Fasmac.. DNA concentration and purity were determinedusing nanodrop spectrofotometry and electrophoresis. DNA isolation showed that the DNA concentration of fresh seafood products was higher than the processed seafood products. DNA isolation using CTAB method have higher levels of DNA purity (1.60-2.00) than using commercial kits in all samples. The commercial kits offer a simple procedure and minimize the possibility of environmental contaminants.